2007
DOI: 10.1111/j.1420-9101.2007.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection maintains whole‐body chiral dimorphism in snails

Abstract: Although the vast majority of higher animals are fixed for one chiral morph or another, the cause for this directionality is known in only a few cases. In snails, for example, rare individuals of the opposite coil are unable to mate with individuals of normal coil, so directionality is maintained by frequency-dependent selection. The snail subgenus Amphidromus presents an unexplained exception, because dextral (D) and sinistral (S) individuals occur sympatrically in roughly equal proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 38 publications
3
93
1
1
Order By: Relevance
“…7; Gittenberger, 1988;Orr, 1991;Ueshima and Asami, 2003). Asami et al (1998) showed that the physical difficulty of interchiral mating differs significantly between the two discrete mating behaviors associated with the bimodal distribution of shell shape in shell-bearing terrestrial pulmonates, although exceptional cases have raised new questions (Sutcharit et al, 2007;Schilthuizen et al, 2007;Davison and Mordan, 2007). Flat-shelled to globular species mate reciprocally face to face (Fig.…”
Section: Chiral Reproductive Isolation and Speciation In Snailsmentioning
confidence: 99%
See 2 more Smart Citations
“…7; Gittenberger, 1988;Orr, 1991;Ueshima and Asami, 2003). Asami et al (1998) showed that the physical difficulty of interchiral mating differs significantly between the two discrete mating behaviors associated with the bimodal distribution of shell shape in shell-bearing terrestrial pulmonates, although exceptional cases have raised new questions (Sutcharit et al, 2007;Schilthuizen et al, 2007;Davison and Mordan, 2007). Flat-shelled to globular species mate reciprocally face to face (Fig.…”
Section: Chiral Reproductive Isolation and Speciation In Snailsmentioning
confidence: 99%
“…The LR polarity of Amphidromus, in which populations of many species are enantiomorphic, is also probably determined by the dextral and sinistral alleles as well (Sutcharit et al, 2007;Schilthuizen et al, 2007). In other animals, however, most cases in which a handedness gene is mutated result in randomized LR polarity , although one exception is the mouse inv mutant (Yokoyama et al, 1993).…”
Section: Short Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence of disassortative mating has been reported in mice (Isles et al 2001;Carroll et al 2002) and humans (Wedekind & Fü ri 1997;Santos et al 2004), and in both cases, females preferred males with odours that differed from their own. However, only a few empirical examples have been reported in the wild (Roulin 2004;Schilthuizen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in snails, rare individuals with anti-clockwise shell coiling are unable to mate with individuals with clockwise shell coiling, so directionality is maintained by frequency-dependent sexual selection (Schilthuizen et al 2007). In our case study, chirality does not represent an isolating barrier as pollinators move pollen (as estimated by pollen-analogue fluorescent dyes) between the two morphs, and hand pollinations confirmed that the two morphs are fully compatible.…”
Section: Discussionmentioning
confidence: 99%